Appraisal of ground water vulnerability to seawater intrusion using the GALDIT method in Northwestern Douala basin, Cameroon - Jovens Nyangang Aduck; Alice Magha Mufur; Mathias Fru Fonteh (Discover Geoscience)
Abstract Aquifer systems in coastal areas provide huge volumes of fresh water for domestic use globally. Seawater intrusion poses a significant challenge to this fresh water reservoir, resulting from excessive extraction, sea level rise, and changing climates. This present study employed GALDIT model and impacts of sea level rise to evaluate the susceptibility of groundwater to contamination by seawater in Northwestern Douala basin. This study also utilized ionic proportions of Na/Cl, Ca/Mg, the Simpson ratio, BEX, alongside USSL. The results revealed the GALDIT index value varied between 3.5 and 3.8, suggesting that the study area exhibits low vulnerability to saline water, as the values are below 5. The southern portion of the study domain, which constitutes 30% of the total area, exhibited higher values of 3.8. According to the GALDIT index, this region is more susceptible to seawater intrusion compared to other areas. The impact of a 1-m rise in sea level attributed to changes in climate showed that the area with higher values expanded from 30 to 50% of the study region, encompassing the southern part and reaching the central part of the area under investigation. Results from ionic ratios revealed that groundwater contamination is mainly from anthropogenic sources, the USSL classification revealed low salinity and the BEX revealed groundwater within the investigated region is basically undergoing freshening process. The Hydrogeochemical facies showed a predominance of alkaline earth elements over alkali metals (Ca + Mg > Na + K) and a prevalence of weak acidic anions over strong acidic anions (HCO3 > Cl + SO4) which is an indication of low salinization. Significantly, this study would aid to delineate areas with greater risk to sea-water intrusion from the GALDIT model, provide an understanding of the hydrogeochemical dynamics in the study area, and equally serves as a basis for sustainable groundwater management and environmental conservation efforts.